Peculiarities of methodological approach to assessing potential enterprise air transport complex of Ukraine - Новикова, М. В. (Proceedings of National Aviation University (archive), 2013)
The peculiarities of management potential business aviation transport sector. The character and degree of interaction elements of strategic capacities at different stages of the life cycle. The structure and composition of the elements of the mechanism of strategic enterprise potential air transport complex. Formed methodological approach to the evaluation of potential business aviation transport complex.